Institutional transformation through best practices in virtual campus development [ advancing e-learning policies - Connolly, Thomas M.; Stansfield, Mark , 1963- (Information Science Reference, 2009)
"This book helps institutions and key stakeholders understand the diverse issues surrounding e-learning and virtual campus initiatives and the conditions necessary to achieve greater success and sustainability"--Provided by publisher.